2014
DOI: 10.1007/s00216-014-7997-z
|View full text |Cite
|
Sign up to set email alerts
|

A fluorogenic heterogeneous immunoassay for cardiac muscle troponin cTnI on a digital microfluidic device

Abstract: We describe a fluorogenic two-site noncompetitive heterogeneous immunoassay with magnetic beads on a low-voltage digital microfluidic platform using closed electrowetting-on-dielectric (EWOD). All the steps of an enzyme-linked immunosorbent assay (ELISA) were performed on the device using 9H-(1, 3-dichloro-9, 9-dimethylacridin-2-one-7-yl) phosphate as the fluorogenic substrate for the enzyme alkaline phosphatase. The performance of the system was demonstrated with cardiac marker Troponin I (cTnI) as a model an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 28 publications
0
19
1
Order By: Relevance
“…5 C). The detection limit was 0.19 ng/mL, as calculated from 3σ/S, which was superior to those previously reported assay for cTnI detection ( Table S3 ) ( Liu et al, 2016 ; Wu et al, 2010 , 2017 ; Guo et al, 2019 ; Song et al, 2011 ; Dorraj et al, 2015 ; Zuo et al, 2016 ; Tsaloglou et al, 2014 ; Periyakaruppan et al, 2013 ). Comprehensive consideration of performance, cost, and detection time, our method still showed obvious overall advantages compared with other fluorescence-based methods ( Liu et al, 2020 , Liu et al, 2020 , Liu et al, 2020 ; Jarvenpaa et al, 2012 ; Zhao et al, 2019 ; Liu et al, 2020 , Liu et al, 2020 , Liu et al, 2020 ) ( Table S4 ).…”
Section: Resultscontrasting
confidence: 48%
“…5 C). The detection limit was 0.19 ng/mL, as calculated from 3σ/S, which was superior to those previously reported assay for cTnI detection ( Table S3 ) ( Liu et al, 2016 ; Wu et al, 2010 , 2017 ; Guo et al, 2019 ; Song et al, 2011 ; Dorraj et al, 2015 ; Zuo et al, 2016 ; Tsaloglou et al, 2014 ; Periyakaruppan et al, 2013 ). Comprehensive consideration of performance, cost, and detection time, our method still showed obvious overall advantages compared with other fluorescence-based methods ( Liu et al, 2020 , Liu et al, 2020 , Liu et al, 2020 ; Jarvenpaa et al, 2012 ; Zhao et al, 2019 ; Liu et al, 2020 , Liu et al, 2020 , Liu et al, 2020 ) ( Table S4 ).…”
Section: Resultscontrasting
confidence: 48%
“…15,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Based on the phenomenon of electrowettingon-dielectric (EWOD), droplets with a wide range of volumes (microliter to sub-nL) can be individually manipulated using forces generated by an array of microelectrodes. EWOD-based chips (also known as digital microfluidics) have been used to perform molecular assays such as detection of single nucleotide polymorphisms, 48 DNA amplification, 15,49-51 immunoassays [52][53][54][55] and automated library preparation for next generation sequencing. 56 EWOD devices require very small volumes of reagent and manipulate and process precise droplet volumes, improving the assay performance (reviewed by Shen et al 57 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rackus et al [36] reported the first integration of nanostructured microelectrodes (NME) with a DMF platform to execute an electrochemical immunosensing for rubella virus (see Figure 6A); the sensitivity of the detection of this immunosensing is 0.07 IU/mL (5.7 μg/mL). Tsaloglou et al [120] described a heterogeneous immunoassay with magnetic beads on a DMF platform to detect the cardiac marker Troponin I (cTnI); the sensitivity of the detection of this immunosensing is 2.0 ng/mL. Zeng et al [62] reported the first experiment to integrate a portable prototype of a CL detector on a DMF platform (see Figure 6B); they manipulated the ball-like droplet to focus better the enzymatic chemiluminescence and thus enhanced the detection sensitivity of the optical signal.…”
Section: Electrowetting-on-dielectric (Ewod) Digital Microfluidic Devmentioning
confidence: 99%